DETERMINAÇÃO DE ÁCIDO α-LIPÓICO EMPREGANDO TÉCNICAS ELETROQUÍMICAS E ANÁLISE POR INJEÇÃO EM BATELADA - Pereira, Laise Nayra dos Santos (2014)
This work describes the development of electroanalytical procedures for α-lipoic acid (ALA) determination in dietary supplement using a pyrolitic graphite electrode (PG) modified with cobalt phthalocyanine (CoPc) from electrochemical techniques and by Batch Injection Analysis (BIA). Cyclic voltammograms of ALA oxidation on the PG/ CoPc electrode presented an irreversible peak ~+0.85 V vs Ag/ AgCl, a value about 100 mV to less positive potential, well as a significant increase in the magnitude of peak current compared to the PG electrode unmodified. The analytical curves obtained with cyclic voltammetry (CV), differential pulse voltammetry (DPV) and chronoamperometry showed good linearity and sensitivity. The DPV technique showed the best values of limit of detection (LOD) and quantification (LOQ) 3.4 x 10ˉ⁹ mol Lˉ¹ and 1.2 x 10ˉ⁸ mol Lˉ¹, respectively. Therefore was chosen for determination of ALA on technique. Voltammetric response of ALA was also evaluated in PG electrode unimodified and modified in hydrodynamic conditions. The modification of the PG/ CoPc electrode produced an increase of 2.33 times compared to the PG electrode. The analytical method was then proposed using the PG/ CoPc electrode for detection of ALA by BIA. The method showed a good linear range between (1.0 x 10ˉ⁶ to 1.0 x 10ˉ⁴ mol Lˉ¹), values of LOD and LOQ of 1.5 × 10ˉ⁸ mol Lˉ¹ and 5.0 × 10ˉ⁸ mol L-1, respectively, with analytical frequency of 208 injections/ hour. The quantification of ALA in dietary supplement showed concordant results with those obtained by chromatographic method, with a confidence level of 95%. Recovery tests were performed added a concentration of ALA in a sample of synthetic urine, where the recovery values were in the range 98 - 107%.